Solid-phase synthesis for thalidomide-based proteolysis-targeting chimeras (PROTAC) - Krajcovicova, S; Jorda, R; Hendrychova, D; Krystof, V; Soural, M (Chemical communications (Cambridge, England), 2019)
A preloaded resin consisting of a thalidomide moiety and an ethylene-oxy linker allows the simple and fast formation of PROTACs. The feasibility of the procedure was illustrated by conjugating different protein kinase inhibitors. The biological functionality of an ibrutinib-like conjugate was then confirmed by a cellular experiment.